Mechanism of dissolution of minium (Pb3O4) in water under depleting chlorine conditions. (February 2016) - Guo, Daoping; Robinson, Clare; Herrera, Jose E.
Graphical abstract: Highlights: Pb3 O4 is unstable under typical drinking water conditions. Pb3 O4 dissolution under drinking water conditions is triggered by a nucleophilic attack on the Pb(II) centers present in the solid. Under typical drinking water conditions carbonate precipitation regulates lead solubility after chlorine depletion. Part of the dissolved lead reprecipitates on the Pb3 O4 surface as β-PbO2 . Abstract: Long-term batch dissolution experiments were performed on solid phase Pb3 O4 under drinking water conditions simulating a depleting chlorine regime. Analytical and spectroscopic results indicate Pb3 O4 is first dissolved in the presence of chlorine through a nucleophilic attack to the Pb 2+ centers in the solid, and is subsequently oxidized by free chlorine to form β-PbO2, with a concomitant decrease in soluble lead concentrations. Following chlorine depletion, Pb3 O4 dissolution regulates the process, resulting in surface deposition of β-PbO2 . Formation of lead carbonates controls the final observed lead concentrations for Pb3 O4 dissolution. A dissolution model is presented to rationalize these observations.